Tuning Conductivity and Spin Dynamics in Few-Layer Graphene via In Situ Potassium Exposure - Márkus, Bence Gábor; Sági, Olivér; Kollarics, Sándor; Edelthalhammer, Konstantin; Hirsch, Andreas; Hauke, Frank; Szirmai, Péter; Náfrádi, Bálint; Forró, László; Simon, Ferenc (physica status solidi (b), 2020)
Chemical modification such as intercalation or doping of novel materials is of great importance for exploratory material science and applications in various fields of physics and chemistry. Herein, the systematic intercalation of chemically exfoliated few-layer graphene with potassium is reported while monitoring the sample resistance using microwave conductivity. It is found that the conductivity of the samples increases by about an order of magnitude upon potassium exposure. The increased number of charge carriers deduced from the electron spin resonance (ESR) intensity also reflects this increment. The doped phases exhibit two asymmetric Dysonian lines in ESR, a usual sign of the presence of mobile charge carriers. The width of the broader component increases with the doping steps; however, the narrow components seem to have a constant line width.
CRIS-Team Scopus Importer:2020-10-09
Keywords: charge transfer; doping; electron spin resonance; intercalation; spintronics